Nrf2 Negatively Regulates Type I Interferon Responses and Increases Susceptibility to Herpes Genital Infection in Mice - Gunderstofte, Camilla; Iversen, Marie Beck; Peri, Suraj; Thielke, Anne; Balachandran, Siddharth; Holm, Christian Kanstrup; Olagnier, David (Frontiers in Immunology, 2019)
Herpes simplex virus-2 (HSV-2) is a leading cause of sexually transmitted infections for which no effective vaccines or prophylactic treatment currently exist. Nuclear factor erythroid 2-related factor 2 (Nrf2) is a transcription factor involved in the detoxification of reactive oxygen species (ROS) and has been more recently shown to regulate inflammatory and antiviral responses. Here, we evaluated the importance of Nrf2 in the control of HSV-2 genital infection and its role in the regulation of HSV-induced innate antiviral immunity. Comparison of antiviral gene expression profile by RNA-sequencing analysis of wild type and Nrf2-mutant (Nrf2AY/AY) mutant murine macrophages showed an upregulation at the basal level of the type I interferon-associated gene network. The same basal increased antiviral profile was also observed in the spleen of Nrf2-/- mice. Interestingly, the lack of Nrf2 in murine cells was sufficient to increase the responsiveness to HSV-derived dsDNA and protect cells from HSV-2 infection in vitro. Additionally, genetic activation of Nrf2 in Keap1-/- mouse embryonic fibroblasts increased HSV-2 infectivity and replication. Finally, using an in vivo vaginal herpes infection model we showed that Nrf2 controlled early innate immune responses to HSV-2. Nrf2-/- mice exhibited reduced viral replication that was associated with higher level of type I interferons in vaginal washes. Nrf2-/- mice also displayed reduced weight loss, lower disease scores and higher survival rates than wild type animals. Collectively, these data identify Nrf2 as a negative regulator of the interferon-driven antiviral response to HSV-2.